Tongue strength and endurance: Comparison in active and non-active young and older adults. (2nd January 2017) - VanRavenhorst-Bell, Heidi A.; Mefferd, Antje S.; Coufal, Kathy L.; Scudder, Rosalind; Patterson, Jeremy
Abstract: Purpose : Tongue strength and endurance are important for swallowing and upper airway patency. Physical activity positively affects targeted and non-targeted skeletal muscles; however, little is known about the indirect effect of physical activity on tongue muscles. This study sought to determine if tongue muscle performance differs between highly active and non-active individuals and if such an effect varies with age. Method : Forty-eight healthy adults were divided into two age groups (24 young, 20.96 ± 3.22 years; 24 older, 65 ± 3.72 years) and further divided into highly active and non-active based on The General Practice Physical Activity Questionnaire. Tongue strength (TS) and tongue endurance (TE) were obtained using the Iowa Oral Performance Instrument. Result : A significant main effect of activity level on TS and TE was found. Although the main effect of age on TS and TE and age × activity level interactions were not significant, the effect of activity level on TS and TE was more pronounced in older adults than younger adults. Conclusion : Findings suggest physical activity may affect TS and TE, particularly in older adults. Future research is warranted to understand the underlying mechanisms contributing to these group differences. Clinical implications of these findings are discussed.